2019
DOI: 10.1038/s41598-019-42892-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological boost of DNA damage response and repair by enhanced biogenesis of DNA damage response RNAs

Abstract: A novel class of small non-coding RNAs called DNA damage response RNAs (DDRNAs) generated at DNA double-strand breaks (DSBs) in a DROSHA- and DICER-dependent manner has been shown to regulate the DNA damage response (DDR). Similar molecules were also reported to guide DNA repair. Here, we show that DDR activation and DNA repair can be pharmacologically boosted by acting on such non-coding RNAs. Cells treated with enoxacin, a compound previously demonstrated to augment DICER activity, show stronger DDR signalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 60 publications
4
51
0
1
Order By: Relevance
“…Alternatively, sirtuinactivating compounds (STACs) could be designed to promote the upstream pathways of DNA repair [58]. Another approach is to increase genome maintenance by artificially promoting the DDR signaling cascade, as proposed by Gioia et al [59], although caution should be taken because, paradoxically, chronic DDR activation can accelerate aging by inducing senescence. In the future, we will need to engage in more intense and multidisciplinary research to fully understand the biochemical and biological steps of aging and move forward to develop plausible strategies that prevent the underlying causes.…”
Section: Prevention Of Agingmentioning
confidence: 99%
“…Alternatively, sirtuinactivating compounds (STACs) could be designed to promote the upstream pathways of DNA repair [58]. Another approach is to increase genome maintenance by artificially promoting the DDR signaling cascade, as proposed by Gioia et al [59], although caution should be taken because, paradoxically, chronic DDR activation can accelerate aging by inducing senescence. In the future, we will need to engage in more intense and multidisciplinary research to fully understand the biochemical and biological steps of aging and move forward to develop plausible strategies that prevent the underlying causes.…”
Section: Prevention Of Agingmentioning
confidence: 99%
“…Previously discussed reports suggested the inhibition of HR/NHEJ and DDR foci formation after Drosha or Dicer knockdown [13,61,77,78], as well as in response to antisense oligonucleotides (ASOs)-mediated dilncRNA inactivation [69]. However, the promotion of NHEJ mediated DNA repair and the reduction in HR efficiency was recently observed after stimulating Dicer activity by enoxacin, suggesting that increasing Dicer activity, and in response to this, DDRNAs production, in some cases modulates the accuracy of DSB repair [79]. Additionally, researchers also elucidated the role of DDRNAs in the stimulation of 53BP1 foci formation [63,78,79], one of the key factors involved in choosing the DBS repair pathway by promoting NHEJ and inhibiting HR [80].…”
Section: Dna Damage Response Small Rna (Ddrna)mentioning
confidence: 99%
“…However, the promotion of NHEJ mediated DNA repair and the reduction in HR efficiency was recently observed after stimulating Dicer activity by enoxacin, suggesting that increasing Dicer activity, and in response to this, DDRNAs production, in some cases modulates the accuracy of DSB repair [79]. Additionally, researchers also elucidated the role of DDRNAs in the stimulation of 53BP1 foci formation [63,78,79], one of the key factors involved in choosing the DBS repair pathway by promoting NHEJ and inhibiting HR [80]. The role of 53BP1 in the regulation of DNA repair and the generally prevailing view of competition between NHEJ and HR support the results presented by Gioia et al [79].…”
Section: Dna Damage Response Small Rna (Ddrna)mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems unlikely that this can be achieved by targeting genomic instability, as several crucial issues would need to be overcome. Although over the last few years several studies have reported that DNA repair can be selectively improved (Georgiadis et al 2016;Gioia et al 2019;Mason et al 2014), this can be a dangerous endeavor, as it is often dysregulated DNA repair (Curtin 2012)-instead of absent repair-that leads to genomic instability, and hyperactive DNA repair has been linked to carcinogenesis as well (Bryant et al 2019;Herrero et al 2015;Sy et al 2020). Moreover, DNA damage occurs largely stochastic, both in its nature and in genomic location, and through a range of different processes, and so the spectrum of lesions will be different from cell to cell.…”
Section: Targeting Proteome Instability To Break a Vicious Cycle Of Dmentioning
confidence: 99%